2006
DOI: 10.1002/art.21724
|View full text |Cite
|
Sign up to set email alerts
|

The association of meniscal pathologic changes with cartilage loss in symptomatic knee osteoarthritis

Abstract: Objective. To explore the role of meniscal tears and meniscal malposition as risk factors for subsequent cartilage loss in subjects with symptomatic osteoarthritis (OA).Methods. Study subjects were patients with symptomatic knee OA from the Boston Osteoarthritis of the Knee Study. Baseline assessments included knee magnetic resonance imaging (MRI) with followup MRI at 15 and 30 months. Cartilage and meniscal damage were scored on MRI in the medial and lateral tibiofemoral joints using the semiquantitative whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

27
414
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 454 publications
(445 citation statements)
references
References 24 publications
27
414
1
3
Order By: Relevance
“…Loading and cartilage wear within the medial compartment appear to vary depending on factors such as the integrity of the anterior cruciate ligament (18,30,31), meniscal status (32,33), and joint malalignment (18,31). For example, one study found the greatest cartilage wear in the anterior regions in medial knee OA (34), whereas others have shown greater involvement in the posterior regions (18,31).…”
Section: Discussionmentioning
confidence: 99%
“…Loading and cartilage wear within the medial compartment appear to vary depending on factors such as the integrity of the anterior cruciate ligament (18,30,31), meniscal status (32,33), and joint malalignment (18,31). For example, one study found the greatest cartilage wear in the anterior regions in medial knee OA (34), whereas others have shown greater involvement in the posterior regions (18,31).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the pain and loss of function associated with a meniscal tear, damage and degenerative changes in the meniscus ultimately lead to loss of cartilage and development of OA [13,29,49,60], with 2 . 3 of patients having radiographic knee OA develop within 5 to 15 years [37].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, both partial meniscectomy and partially healed meniscal incisions in a canine model were shown to result in significant increases in cartilage chondropathy and decreased cartilage tensile properties (12). Furthermore, studies in patients with symptomatic knee OA have revealed that both meniscal damage and malposition are associated with an increased risk of cartilage loss (16). In patients with medial meniscal tears and extrusion, there is also a loss of medial cartilage volume and rapid disease progression in the medial compartment of the joint (17).…”
mentioning
confidence: 99%